Kebijakan Uang Kompensasi Pada Pekerja Dengan Hubungan Perjanjian Kerja Waktu Tertentu (PKWT) - Louvita Achmad S; Dhoni Marten; Mardi Chandra (SALAM: Jurnal Sosial dan Budaya Syar-i, 2021)
Legal protection and welfare for workers is the duty of the government. So far, there is no policy for guarantees that are clearly regulated regarding compensation for workers at the end of their PKWT, such as severance pay for permanent workers. One form of government protection at this time is by making a policy in the form of guarantees in the form of revising Law Number 13 of 2003 concerning Manpower with Law Number 11 of 2020 concerning Job Creation and its derivatives Government Regulation of the Republic of Indonesia Number 35 of 2021 concerning Work Agreements for a certain time, Outsourcing, Working Time and Rest Time, and Termination. The government's protection that is made is to require employers/companies to provide compensation money to workers with a Specific Time Employment Agreement (PKWT) or to contract workers. This compensation money is in the form of wages, which can be in the form of basic salary or accumulated with fixed allowances depending on the wage reference of the employer/company. This compensation money will have to be given at the end of the PKWT for workers or it can be given in accordance with the PKWT period that has been implemented if the PKWT ends prematurely. It is hoped that with this compensation policy, contract workers can be more protected and prosperous even though the PKWT for themselves ends.Keywords: Compensation Money; Workers; PKWT; Job Creation Law; PP 35 of 2021 AbstrakPerlindungan hukum dan kesejahteraan bagi pekerja adalah tugas bagi pemerintah. Selama ini tidak ada kebijakan adanya jaminan yang diatur jelas mengenai kompensasi bagi pekerja diakhir PKWT-nya, seperti halnya pesangon bagi pekerja tetap. Salah satu bentuk perlindungan Pemerintah saat ini adalah dengan membuat kebijakan berupa jaminan berupa merevisi Undang-Undang Nomor 13 Tahun 2003 Tentang Ketenagakerjaan dengan Undang-Undang Nomor 11 Tahun 2020 Tentang Cipta Kerja dan turunannya Peraturan Pemerintah Republik Indonesia Nomor 35 Tahun 2021 Tentang Perjanjian Kerja Waktu tertentu, Alih Daya, Waktu Kerja dan Waktu Istirahat, dan Pemutusan Hubungan Kerja. Perlindungan pemerintah yang dibuat adalah mewajibkan pemberi kerja/ perusahaan memberikan uang kompensasi kepada pekerja dengan Hubungan Perjanjian Kerja Waktu Tertentu (PKWT) atau untuk pekerja kontrak. Uang kompensasi ini berupa upah, yang dapat berupa gaji pokok atau diakumulasi dengan tunjangan tetap tergantung dengan acuan upah pada pemberi kerja/ perusahaan. Uang kompensasi ini nantinya harus diberikan di akhir PKWT pekerja atau dapat diberikan sesuai dengan jangka waktu PKWT yang telah dijalankan jika PKWT berakhir sebelum waktunya. Diharapkan dengan kebijakan uang kompensasi ini, pekerja kontrak dapat lebih terlindungi dan sejahtera walaupun PKWT atas dirinya berakhir.Kata Kunci :Uang Kompensasi; Pekerja; PKWT; UU Cipta Kerja; PP 35 Tahun 2021